2013
DOI: 10.1515/lp-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

Optionality and locality: Evidence from Navajo sibilant harmony

Abstract: While many phonological processes are local, consonant harmony is of interest phonologically because it can occur non-locally. Sibilant harmony in Navajo requires that sibilants within a word have matching anteriority specifications. The process is described as being sometimes mandatory and sometimes optional, but neither the statistical nature of the occurrence in optional settings nor the factors contributing to the optionality are fully understood. This paper provides preliminary investigation into these is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…As in the dictionary corpus, however, the harmony preference is comparable for both anterior-postalveolar and postalveolar-anterior combinations. The relatively weak harmony preference is consistent with Berkson's (2013) findings working with contemporary speakers and web data. In contrast, the dictionary word forms are carefully elicited and reflect data collected at an earlier time, unlike the more current and uncurated web data.…”
Section: Web Word Corpussupporting
confidence: 90%
See 1 more Smart Citation
“…As in the dictionary corpus, however, the harmony preference is comparable for both anterior-postalveolar and postalveolar-anterior combinations. The relatively weak harmony preference is consistent with Berkson's (2013) findings working with contemporary speakers and web data. In contrast, the dictionary word forms are carefully elicited and reflect data collected at an earlier time, unlike the more current and uncurated web data.…”
Section: Web Word Corpussupporting
confidence: 90%
“…Martin (2011) looked at 211 compounds with multiple stridents, and found that harmony held 70% of the time for stridents in adjacent syllables and 44% of the time for stridents in non-adjacent syllables. Berkson (2013) found that evidence for harmony in the 1 st singular possessive prefix [ʃi]~[si] ([ʃi] in forms with no stridents) was weak, across several different measures: the [ʃi-] form was preferred for all roots in a judgment study of orthographic forms, a small production study found consistent production of the prefix as [ʃi-], and very low rates of harmony were found in an analysis of online written Navajo assessed via the number of Google hits. Both of these findings suggest that harmonic alternations are both variable and perhaps undergoing change.…”
mentioning
confidence: 99%
“…Not all phonological patterns, however, obey this criterion of locality; some languages contain long-distance patterns in which two segments interact in some way, but can be separated by an arbitrary number of other segments. One long-distance pattern is sibilant harmony (Rose and Walker 2004), and while not exceedingly common, it is attested in a variety of unrelated languages such as in Navajo (Na-Dene: Berkson 2013), in Aari (Omotic : Hayward 1990), and in Slovenian (Indo-European: Jurgec 2011). In a typical sibilant harmony system, all sibilants within a given word must agree in anteriority, meaning that a wordinternal sequence of a [-ant] sibilant followed by a [+ant] sibilant (e.g., [ʃ…s]), or vice versa, must be repaired so that both sibilants are [-ant] or both sibilants are [+ant].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this holds no matter how many sounds intervene between the two sibilants. Take for instance the data in (1) from Navajo (Berkson 2013). The first-person possessive prefix is underlyingly /ʃi-/ and surfaces as such when it attaches to a word containing no sibilants (1a) or containing /ʃ/ (1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation